J.A.G. Roberts: China to Chinatown. Chinese Food in the West - Dalby, Andrew (Petits Propos Culinaires, 2024)
J.A.G. Roberts: China to Chinatown. Chinese Food in the West: Reaktion, 2002: ISBN 1861891334: 255 pp., h/b, £19.95.